Antimonial therapy induces circulating proinflarnmatory cytokines in patients with cutaneous leishmaniasis - Kocyigit, A; Gur, S; Gurel, MS; Bulut, V; Ulukanligil, M (Amer Soc Microbiology, 2002)
The objective of this study was to evaluate the association between antimonial therapy and circulating levels of proinflammatory cytokines in patients with cutaneous leishmaniasis (CL). Patients were treated with conventional chemotherapy by using pentavalent antimonium salts (Glucantime) for 3 weeks. Circulating plasma levels of the proinflammatory cytokines interieukin-1beta (IL-1beta), IL-6, IL-8, and tumor necrosis factor alpha (TNF-alpha) were determined for CL patients and healthy subjects before and 3 weeks after the treatment was started. Plasma IL-1beta, IL-6, IL-8, and TNF-alpha levels were significantly higher for pretreatment CL patients than for healthy subjects. Proinflammatory cytokines significantly increased after 21 days postinfection compared to levels for the pretreatment patients. These increments were approximately Mold for IL-1beta and TNF-alpha levels, 10-fold for IL-6 levels, and 20-fold for IL-8 levels in patients with CL. Taken together these results indicate that circulating proinflammatory cytokine levels were increased in patients with CL as a consequence of host defense strategies, and antimonial therapy may induce these cytokines by affecting the macrophage or other components of the host defense system.
Keywords: Sodium Stibogluconate; Nitric-Oxide; Ifn-Gamma; Macrophage; Induction; Interleukin-8; Lymphokines; Infection; Cells